Both Weight at Age 20 and Weight Gain Have an Impact on Sleep Disturbances Later in Life: Results of the EpiHealth Study. Issue 1 (19th January 2018) - Cai, Gui-Hong; Janson, Christer; Theorell-Haglöw, Jenny; Benedict, Christian; Elmståhl, Sölve; Lind, Lars; Lindberg, Eva
Abstract: Study Objectives: Obesity is often associated with impaired sleep, whereas the impact of body mass index (BMI) at younger age and previous weight gain on sleep problems remains unknown. Methods: The present study utilized data from the Swedish EpiHealth cohort study. A total of 15845 participants (45–75 years) filled out an internet-based questionnaire. BMI was calculated from both measured data at study time and self-reported data at age 20 from the questionnaire. Results: Sleep-related symptoms were most common among obese individuals (BMI > 30 kg/m 2 ). An association between weight gain and sleep problems was found and those with a low BMI at age 20 were most vulnerable to weight gain when it came to risk of sleep problems. Among those who were underweight (BMI < 18.5 kg/m 2 ) at age 20, weight gain (kg/year) was associated with difficulties initiating sleep with an adjusted OR of 2.64 (95% CI: 1.51–4.62) after adjusting for age, sex, smoking, alcohol consumption, physical activity, education, and civil status. The corresponding adjusted OR's among those who had been normal weight (BMI 18.5–24.99) and overweight (BMI 25–29.99 kg/m 2 ) at age 20 were 1.89 (1.47–2.45) and 1.02 (0.48–2.13), respectively. Also difficulties maintaining sleep and snoring were most strongly related to weight gain among those who were underweight at age 20 with decreasing odds with increasing BMI at that age. Conclusions: Sleep problems are related to weight gain and obesity. The impact of weight is most pronounced among those who had a low BMI when young.